STRATEGI PENINGKATAN KUALITAS PELAYANAN MEDIK PADA RSUD. KOTAPINANG KABUPATEN LABUHANBATU SELATAN TAHUN 2020 - Khalijah, Siti (Jurnal Kajian Kesehatan Masyarakat, 2021)
Hospitals are always required to improve the quality, scope and efficiency of hospital services through improving and developing hospital management, especially from human resources, funding and information towards hospital independence while still paying attention to their social functions. In providing complete health services to the community, the hospital must always pay attention to all aspects that play an important role. This study aims to describe the relevant strategies to be implemented by the RSUD. Kotapinang in improving the quality of services obtained as a result of the recommendations from the SWOT analysis using qualitative descriptive research conducted from January to June 2020. This study used snowball sampling techniques with initial informants as many as 5 directors consisting of: Head of Kotapinang District Hospital, Labuhanbatu Selatan District, Head of Medical Services, General Hospital of Kotapinang District Hospital, Inpatients in Kotapinang District Hospital and Patients who visited Kotapinang District Hospital. The results of the study concluded that it was necessary for the Regional Hospital. Kotapinang Regency of South Labuhanbatu needs to work on self-improvement through improving the quality and quantity of work supporting facilities and facilities in the delivery of health services and Striving for the use of information technology systems in assisting the service process while seeking access to the procurement of high technology products in the health sector to support increased quality of service.